Risk assessment of pressure injuries in newborns. Appropriateness of Glamorgan and NSRAS scales: a scoping review - Biagio Nicolosi; Felice Curcio; Maria Aurelia Gheorghe; Prisco Ranieri; Eustachio Parente (Firenze University Press, 2024)
The newborn's skin must undergo a transition process as a result of the passage from an aqueous to an aerobic environment. This process occurs over a period of approximately 2 to 8 weeks. The skin of newborns has important anatomical and physiological differences compared to those of older children and adults. It is thin, with fewer appendages; the stratum corneum is not present; the dermal-epidermal junction is reduced; intercellular junctions are weaker; the secretions of the sebaceous glands are limited and the pH is generally neutral. All these factors make the newborn's skin more fragile to any stimulus. To have effective prevention and intervention procedures, an accurate and practical risk assessment tool should be identified as a preliminary step for adequate prevention. Unfortunately, only few validated tools are available to assess the risk of PUs in children, especially newborns. The objective of the study is to examine the adherence of the most used tools for the assessment of PU risk in newborns, in particular to make a comparison of the limits and advantages of the most frequently used tools in neonatal settings, the Glamorgan scale and NSRAS. To respond to the main objective, a scoping review of the literature was conducted. 54 studies were identified. Further analysis was conducted, which led to the exclusion of articles that did not examine the characteristics of newborn skin, the risk factors related to PUs and the appropriateness of the NSRAS and Glamorgan tools, for a final selection of 35 studies. Patients admitted to NICU represent the paediatric category most exposed to the risk of developing pressure ulcers. Factors such as reduced mobility, together with the pressure exerted by aids or devices, increase the risk of pressure injuries. The risk factors that most expose the newborn to risk are the structure of the skin and medical devices. Nurses should implement preventative measures to control the risk of PU. The use of specific tools is necessary to detect the risk of PUs in newborns and implement preventive measures. PUs risk assessment is one of the nursing care strategies for prevention. Therefore, operators need a valid, reliable, and predictive scale. Lastly, we recommend the use of NSRAS for future research and for the education of healthcare professionals in the neonatal area.